Efficacy of Different Approaches to Control Litchi Fruit Borer (Bangladesh Journal of Agricultural Research, 2023)
Litchi is affected by number of pests, among them litchi fruit borer (LFB), Conopomorpha sinensis Bradley (Lepidoptera: Gracillariidae) is serious one which causes considerable yield loss. This study aimed to evaluate the efficacy of different options for the management of LFB. The research work was conducted in an orchard at Gopalpur under Tangail district of Bangladesh consecutively for two seasons to manage LFB using mosquito net, two types of bags, three botanicals and five synthetic insecticides as spray material to find out the most efficient one based on the highest reduction of fruit infestation (RFI) over control along with benefit cost ratio (BCR). White butter paper bagging showed highest RFI (100%) with 51.66% increase of fresh fruit (FF) over control and BCR 7.47:1. Neem oil was significantly effective in RFI over control (78.73%) with BCR 8.67:1. Novastar 56 EC (Bifenthrin+ Abamectin) was the most effective among the chemical treatments recording 98.08 % RFI with increase of 51.18 % FF over control and BCR 6.06:1. Based on BCR, performance of different treatments could be ranked as Neem oil > Paper bagging > Novastar. So, Paper bagging as safe technique, Neem oil at the rate of 6 ml/L of water as an eco-friendly tactic and Novastar 56 EC @ 1 ml/L of water as least harmful approach could be recommended to protect litchi from the attack of LFB and ensure higher number of fresh fruits.Bangladesh J. Agril. Res. 46(2): 143-151, June 2021